2013
DOI: 10.1253/circj.cj-13-0626
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pulmonary Arterial Pressure by Velocity-Encoded Cine Magnetic Resonance Imaging in Children With Congenital Heart Disease

Abstract: Background: Velocity-encoded cine magnetic resonance imaging (VEC-MRI) has recently been reported as effective for assessing not only pulmonary blood flow (Qp) but also pulmonary arterial pressure (PAP) in adults. However, there have been few reports on the usefulness of VEC-MRI for assessing PAP in children with congenital heart disease (CHD). Methods and Results:We evaluated 34 children with CHD. Qp and systemic blood flows (Qs) were determined by cardiac catheterization and VEC-MRI. The right-to-left Qp rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our results showed that there was an extremely good correlation between Qp/Qs values obtained using VEC-MRI and those obtained using oximetry with cardiac catheterization (Fig. 8.13) [26].…”
Section: Investigation Of Usefulness In Pediatric Patientssupporting
confidence: 65%
See 1 more Smart Citation
“…Our results showed that there was an extremely good correlation between Qp/Qs values obtained using VEC-MRI and those obtained using oximetry with cardiac catheterization (Fig. 8.13) [26].…”
Section: Investigation Of Usefulness In Pediatric Patientssupporting
confidence: 65%
“…Our study on pediatric patients showed a good correlation between MCFR assessed using VEC-MRI and pulmonary arterial systolic pressure assessed using cardiac catheterization ( Fig. 8.18) [26]. BSA body surface area, sPAP systolic PAP, mPAP mean PAP, dPAP diastolic PAP, Qp/Qs the ratio of pulmonary to systemic blood flow, Pp/Ps the ratio of pulmonary to systemic blood pressure, Rp pulmonary arterial vascular resistance…”
Section: Estimation Of Pulmonary Arterial Pressure By Using Vec-mrimentioning
confidence: 53%
“…27,62,63 Mousseaux et al 62 documented a strong correlation between PVR and the quotient of maximum change in flow rate during ejection by AccV ( r  = 0.89). Moreover, Sugimoto et al 64 found that the maximum change in flow rate during ejection, when normalized to the body surface area, was significantly higher in children with PH than in children without PH and correlated strongly with pulmonary-to-systemic blood pressure ratio in children with PH ( r  = 0.90); the parameters AT, ET, AT/ET, AccV and v peak revealed no significant differences between the PH and non-PH groups.…”
Section: Standard Pc Parameters Of the Main Pulmonary Artery In Phmentioning
confidence: 99%
“…Additionally, cardiac magnetic resonance imaging has also been used to assess pulmonary artery pressure measurements in children with congenital heart disease. Researchers found velocity encoded flow cardiac MRI images strongly correlated with right heart catheterization for systemic blood flow (QS), right to left pulmonary blood flow (QP) ratio and QP/QS ratio[ 47 ]. This suggests usefulness of cardiac MRI for pulmonary artery pressure measurement by using the standard SSFP cine imaging and phase contrast flow imaging.…”
Section: Literature Searchmentioning
confidence: 99%